A short history of the international economy, 1850-1950 - Ashworth, William (London ; New York : Longmans, Green, 1952)
The book is in three main parts. The first two chapters show how from small beginnings world production rapidly expanded and how the growth of activity in one group of occupations and in one region stimulated similar growth in other occupations and other parts of the world, thus establishing new links of international dependence and promoting a changing international specialization of economic functions. Chapters III - V present some of the main changes in the organization and regulation of economic activity which have been common to the most commercially advanced countries. The last three chapters discuss the course of international economic relations within this setting of expanding production and changing organization and policy.
Includes index.
aia 13/11/2017
Loans
Keywords: Economic history